PENGARUH PROFITABILITAS DAN LEVERAGE TERHADAP NILAI PERUSAHAAN PADA PT GUDANG GARAM TBK TAHUN 2013 - 2022 - Citra Indrawati Kusuma Wardani; Lily Setyawati Kristianti (Journal of Research and Publication Innovation, 2025)
The thesis writing aims to determine whether there is an effect of Profitability and Leverage on Company Value at PT Gudang Garam Tbk for the period 2013 - 2022. The population used is the entire financial statements of PT Gudang Garam Tbk for the period 2013 - 2022 and the sample used is the statement of financial position and income statement. The research method used is quantitative method. The analysis technique used is descriptive analysis, classical assumption test, multiple linear regression test, correlation coefficient test, determination coefficient test, partial test (T test), simultaneous test (F test). The results of this study indicate that partially the profitability variable has no significant effect on Firm Value with tcount 1.82 < table 1.894 with a prob t value of 0.112> 0.05. Leverage variable partially has a significant effect on Firm Value with a tcount of 2.14> t table 1.894 with a prob t value of 0.070> 0.05. Simultaneously, the Profitability and Leverage variables on Firm Value with Fcount 6.21> Ftable 4.737 with a prob value of F 0.0281> 0.05.